SHadow Under the Lamp (SHUL): Smoking behavior of the health professionals. (30th September 2020) - Rahman, M A; Susanto, A W; Quarashi, A A; Raymond, A; Taufik, F F; Mahmud, I; Al Kloub, M I; Oli, N; Martini, S; Khan, Z
Abstract: Background: Smoking cessation is the best option a health professional can offer to the patients for averting the preventable causes of mortality and morbidity. Purpose: To determine smoking behavior, preferred cessation methods, and attitudes towards smoking cessation amongst health professionals. Methods: The cross-sectional study, conducted in six countries, included doctors and nurses working at different hospital settings. Participants responded anonymously to an online questionnaire. Results: Among 1109 participants, 36% were from Saudi Arabia, 14% from Nepal, 14% from Indonesia, 12% from Australia, 12% from Jordan, and 12% from Pakistan. Mean age was 33 years, 61% were females and 58% were nurses. One in eight (12%) was daily smoker. Among current smokers, 42% smoked 2-9 cigarettes/day, and 26% had their first cigarette within 5-30 minutes after waking up. Half of the smokers perceived it as 'very important' to quit smoking, 30% had tried to quit in the last six months, and 31% preferred to have a group quit program with the same health professionals. Only 17% had formal training on smoking cessation, but 57% were interested to receive one. Half of the participants said they (53%) 'always' asked patients if they smoked, but 89% said they advised to quit, 76% said they assessed intention to quit, 28% said they assisted by providing materials on cessation, and 33% said they arranged follow up for cessation. Compared to current smokers, never smokers were more likely to 'always' ask patients if they smoked (78% vs. 22%, p = 0.044, ORs 1.39, 95%CIs 1.01-1.91), assist smokers by setting quit dates (74% vs. 26%, p = 0.039, ORs 1.54, 95%CIs 1.03-2.29), arrange follow up (77% vs. 23%, p = 0.044, ORs 1.40, 95%CIs 1.01-1.94). Conclusions: Health professionals reported moderately good behavior around advice to smokers, but it is much worse among current smokers. Health professionals who smoke should be both encouraged to quit and to better support their patients to do so. Key messages: Smoking cessation support for patients was not good among health professionals, who were smokers. Health professionals need to quit smoking in order to provide better cessation support for patients.